Investigation of x-ray emission from high-current discharges of the PF type - Skladnik-Sadowska, E.; Sadowski, M.J.; Malinowsk, K.; Surala, W.; Zaloga, D.; Paduch, M.; Zielinska, E.; Tomaszewski, K. (Вопросы атомной науки и техники, 2016)
The invited paper reports on measurements of soft x-rays emitted from hot plasmas produced in a modernised
PF-1000U facility. The discharges were performed at the D2-filling with or without a Ne-admixture, under the initial
pressure of 0.9 or 1.5 Torr and at the initial charging voltage equal to 16 or 18 kV. Time-integrated x-ray images
were recorded with a pinhole camera situated side-on, at an angle of 75º to the z-axis. Differences in the pinch
column structure were observed. Time-resolved measurements were performed with four PIN diodes located behind
filtered pinholes. Two couples of PIN diodes (with Be-filters of 7 and 10 μm in thickness) observed 30 mm-diam.
regions which had centres at a distance of 30 and 60 mm form the electrode outlets. From the recorded timeresolved
x-ray signals the electron temperatures (Te) were calculated. For the pure D2-discharges the estimated Te
values ranged from 75 to 250 eV depending on the discharge conditions. For discharges with a Ne-admixture Te values were higher and reached about 800 eV. Описаны измерения мягкого рентгеновского излучения горячей плазмы, генерируемой в модернизированной
установке ПФ-1000U. Разряд происходит в вакуумной камере при напуске дейтерия D2 с добавкой Ne и без, начальное
давление составляло 0,9 и 1,5 Торр, а рабочее напряжение  16…18 кВ. С помощью камеры обскура, расположенной
под углом 75º относительно оси z, зарегистрированы рентгеновские снимки с временным разрешением. Наблюдается
разница в структуре пинча. Измерения с временным разрешением проводились с помощью четырёх диодов,
расположенных за отверстием с фильтром. Две пары диодов (с бериллиевым фильтром толщиной 7 и 10 мкм)
передавали изображение из зон радиусом 30 мм, центры которых находятся на расстоянии 30 и 60 мм от среза
электродов. Анализ сигналов рентгеновского излучения с временным разрешением позволил оценить электронную
температуру (Те). Для разрядов с чистым дейтерием величина электронной температуры варьируется от 75 до 250 эВ в
зависимости от условий разряда. Для разрядов с добавкой неона температура была выше и достигала 800 эВ. Описані вимірювання м’якого рентгенівського випромінювання гарячої плазми, що генерується в
модернізованому пристрої ПФ-1000U. Розряд відбувається у вакуумній камері при напуску дейтерію D2 з домішкою
Ne та без нього, початковий тиск складав 0,9 та 1,5 Торр, а робоча напруга  16…18 кВ. Рентгенівські знімки з
часовим розділенням зареєстровані за допомогою камери обскура, яка знаходилась під кутом 750
відносно осі z.
Спостерігається різниця в структурі пінча. Вимірювання з часовим розділенням проводились за допомогою чотирьох
діодів, що розташовані за отвором із фільтром. Дві пари діодів (з берилієвим фільтром 7 та 10 мкм) передавали
зображення із зон радіусом 30 мм в плазмі, центри діодів розташовано на відстані 30 та 60 мм від електродів. Аналіз
сигналів рентгенівського випромінювання з часовим розділенням дозволив оцінити електронну температуру (Те).
Для розрядів с чистим дейтерієм величина електронної температури змінюється від 75 до 250 еВ в залежності від
умов розряду. Для розрядів з домішкою неону температура сягає 800 еВ.